Late sequelae of congenital cytomegalovirus infection – The urgency of a neonatal approach - Botelho, Teresa (2023)
Introduction: Congenital cytomegalovirus (CMV) infection is the main cause of sensorineural deafness in children. In Portugal, routine screening of the infection during pregnancy is not performed. It is acknowledged that late sequelae may occur in children with congenital infections, even when they are asymptomatic at birth. The aim of this study was to investigate early and late sequelae in children of mothers with positive CMV immunoglobulin (Ig) M and IgG during pregnancy. Materials and Methods: Patients: Children born to mothers with positive CMV IgM and IgG during pregnancy at a Portuguese tertiary hospital between August 2006 and August 2020. Demographic, clinical, and laboratory variables and early and late sequelae were retrospectively assessed. Late sequelae included delayed psychomotor development, sensorineural deafness, and vision changes. Results: In the last 14 years, 31 newborns were born to mothers with positive IgM and IgG during pregnancy in the considered hospital (0.08% of the total number of births). CMV infection was confirmed in six of these children (19.4%), of whom one was symptomatic at birth, with multiorgan involvement, and died at the age of four months. Late sequelae were observed in one patient, specifically learning disabilities and attention-deficit/hyperactivity disorder. No cases of ophthalmological or otorhinolaryngological alterations were identified. Discussion: Although congenital CMV infection is a potentially fatal condition, only one death was reported in the present study sample. Late sequelae were also only observed in one case, which was asymptomatic at birth. Conclusion: These results suggest that the indications for CMV screening during the neonatal period should be reassessed. This is particularly important in asymptomatic newborns, as a way to implement early treatment and prevent late sequelae.